KEMARAHAN DAN KETERKAITANNYA DENGAN PEMBUNUHAN: KAJIAN EKSEGESIS MATIUS 5:21-22 - Lola, James; Marriba, Narsing L.; Silakda, Selfina H. (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2024)
Matthew 5:21-22 is part of Matthew's account of Jesus' sermon on the mount, where Jesus presents several antitheses to the law of Moses. These antitheses are not meant to abolish the law but rather to fulfill it and provide a higher standard for Christians in obeying the law. One of the antitheses relates to the commandment not to murder, where Jesus states that someone who is angry and speaks harshly to their brother or sister is already violating the command not to murder and should be punished. In this article, with a grammatical-historical approach, it is evident that Matthew 5:21-22 teaches about the importance of maintaining a clean heart and healthy relationships with others, as well as showing that righteousness is not only seen in physical actions but also in one's attitudes and thoughts.